An Uncommon Case of Bilateral Peroneal Nerve Palsy following Delivery: A Case Report and Review of the Literature. (10th August 2014) - Bunch, Kristen; Hope, Erica
Abstract : Peroneal nerve palsy is an infrequent but potential complication of childbirth. Bilateral peroneal palsy is particularly rare following delivery with few reported cases. A 38-year-old gravida 1, para 0 underwent a prolonged second stage of labor, was diagnosed with an arrest of descent, and subsequently underwent an uncomplicated primary cesarean section. The patient was diagnosed with bilateral peroneal neuropathy four days after delivery. By two months postpartum, her foot drop had improved by 85% and the remainder of her symptoms resolved. Awareness of the risks of a peroneal neuropathy as well as implementation of preventive measures is important for members of the delivery team. Regional anesthesia during labor is a risk factor for the development of a peroneal neuropathy.